Do perceptions of neighbourhood change match objective reality?. Issue 6 (1st November 2020) - Durmaz-Drinkwater, Bahar; Platt, Stephen; Can-Traunmüller, Işın
ABSTRACT: This study analyses neighbourhood change, its impact on the character of Soho, and to what extent perceptions of change match objective reality. Focusing on three streets (Berwick, Old Compton and Wardour Streets), the research (2008–2018) compares objective evidence of ground floor uses with the perceptions of people living and working in Soho. There was a close match between perceptions and objective measures of change on 4 out of 7 indicators: type of use, business name, locality and business ethnicity. The paper discusses these changes in terms of commercial gentrification that threatens Soho's character.